4h-2h+3=2h+2h

Simple and best practice solution for 4h-2h+3=2h+2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4h-2h+3=2h+2h equation:


Simplifying
4h + -2h + 3 = 2h + 2h

Reorder the terms:
3 + 4h + -2h = 2h + 2h

Combine like terms: 4h + -2h = 2h
3 + 2h = 2h + 2h

Combine like terms: 2h + 2h = 4h
3 + 2h = 4h

Solving
3 + 2h = 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
3 + 2h + -4h = 4h + -4h

Combine like terms: 2h + -4h = -2h
3 + -2h = 4h + -4h

Combine like terms: 4h + -4h = 0
3 + -2h = 0

Add '-3' to each side of the equation.
3 + -3 + -2h = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -2h = 0 + -3
-2h = 0 + -3

Combine like terms: 0 + -3 = -3
-2h = -3

Divide each side by '-2'.
h = 1.5

Simplifying
h = 1.5

See similar equations:

| -9x+x^2=-9 | | -7m+3=31 | | 0.3x-0.5(3-x)=1.3 | | -9x+x^2=9 | | 2s+4b=12 | | 436.6+.37Y=Y | | -5(4p+3)-37=4(3p+3) | | 10y=6y+8 | | 4x^3+4x^2+16x=0 | | 5x-3=-9 | | 18x=54.198 | | 7(c-5)=8(c-6) | | Y-17=11 | | 9=x(9-x) | | -15+8x=8x-8 | | .25x-6=12 | | 9-(2+3)=2(6-2) | | 6+-5n+2n=33+-96 | | 100=25-7.5d | | 3(x+4)+2x=4x+14 | | 2.5x-6=12 | | C+2=3c+9 | | 8.08=-11402x^2+766.68x-6.6669 | | -81x^2+4=0 | | W-9c=8forw | | 3=4(5+6n) | | 6-5n+2n=3-96 | | X^2-5x=864 | | 1.33x-5=7 | | 2a-6+5=2a | | 100+.05x=200 | | y=80x+4 |

Equations solver categories